Differences in expression of genes related to steroidgenesis in abdominal subcutaneous adipose tissue of pregnant women with and without PCOS; a case control study - Neda Emami; Ashraf Moini; Parichehreh Yaghmaei; Vahid Akbarinejad; Maryam Shahhoseini; AliReza Alizadeh (BMC, 2021)
Abstract Background It was reported that steroid-related gene expressions in the adipose tissue (AT) of women differ between women affected with polycystic ovary syndrome (PCOS) and non-PCOS. Although association between PCOS in mother and offspring's health is a crucial issue, there are few studies focusing on AT of pregnant women suffering from PCOS. Our objectives were to determine the differences between mRNA expression levels of key steroid-converting enzymes in abdominal subcutaneous AT of pregnant women afflicted with PCOS and non-PCOS. Methods Twelve pregnant women with PCOS (case) and thirty six non-PCOS pregnant women (control) (1:3 ratio; age- and BMI-matched) undergoing cesarean section were enrolled for the present study. Expressions of fifteen genes related to steriodogenesis in abdominal subcutaneous AT were investigated using quantitative real-time PCR. Results No significant differences were detected with respect to age, BMI (prior pregnancy and at delivery day), gestational period and parity among pregnant women with PCOS and non-PCOS. Most of the sex steroid-converting genes except 17β-Hydroxysteroid dehydrogenases2 (17BHSD2), were highly expressed on the day of delivery in subcutaneous AT. Women with PCOS showed significantly higher mRNA levels of steroidgenic acute regulator (STAR; P < 0.001), cytochrome P450 monooxygenase (CYP11A1; P < 0.05), 17α-hydroxylase (CYP17A1; P < 0.05), and 11β-Hydroxysteroid dehydrogenase (11BHSD1 and 11BHSD2; P < 0.05). The expression of steroid 21-hydroxylase (CYP21) in non-PCOS was fourfold higher than those of women with PCOS (P < 0.001). There were no significant differences between relative expression of aromatase cytochrome P450 (CYP19A1), 3β-hydroxysteroid dehydrogenase (3BHSD1 and 3BHSD2), and 17BHSD family (1, 3, 5, 7, and 12) between the two groups. Conclusion The expression levels of genes related to sex steroids metabolism were similar to age-matched and BMI- matched pregnant non-PCOS and pregnant women with PCOS at delivery day. However, the alterations in gene expressions involved in glucocorticoids and mineralocorticoids metabolism were shown. It is necessary to point out that further studies regarding functional activity are required. More attention should be given to AT of pregnant women with PCOS that was previously ignored.